Sulfur/olefin copolymers as vulcanizing agents for rubber - Colvin Howard; Bull Charles (Rubber Chemistry and Technology, 1995)
Sulfur/olefin copolymers are known as vulcanizing agents for rubber, but synthetic procedures for these materials are poor and there is little in the literature to relate the structure of the copolymer with the vulcanizate properties of the rubber. This study discusses a new suspension process for the preparation of sulfur/dicyclopentadiene and sulfur/dicyclopentadiene/styrene copolymers. The relationship between the sulfur/olefin copolymer and vulcanizate properties is discussed in terms of the structure of the copolymer and other reaction products.
Keywords: Olefin copolymer; Vulcanising agent